Religious Moderation Values in Arabic Language Books at Madrasah Aliyah Level Based on KMA No. 183/2019 - Ahmad Sholihuddin; Khoiru Nidak; Lailatul Zuhriyah (Asalibuna, 2024)
This study focuses on three main objectives: the values of religious moderation in Arabic language textbooks for Madrasah Aliyah (MA) based on KMA No. 183/2019; the development of moderation values in MA Arabic language textbooks; and the implications of integrating moderation values into Arabic language textbooks for MA. Employing a qualitative approach with a library research method, the primary data in this study consists of Arabic textbooks for Grades X, XI, and XII published by the Directorate of KSKK Madrasah, Directorate General of Islamic Education, Ministry of Religious Affairs, in 2020. Data were collected through documentation and analyzed using content analysis. The study findings are as follows: (1) Religious moderation values are presented through Arabic textbooks for Grades X, XI, and XII, encompassing six principles of religious moderation: tawassuth (moderation), tawâzun (balance), i’tidâl (justice), tasâmuh (tolerance), musâwah (equality), and syûrâ (consultation); (2) The development of moderation values is reflected in the integration of scriptural evidence (dalil naqli), such as Quranic verses supporting specific reading texts, the inclusion of reading passages with moderation themes, and the presentation of grammatical structures identified as containing moderation values; (3) The internalization of religious moderation values can be supported through strategies such as embedding moderation themes in learning materials, optimizing teaching approaches that foster critical thinking and moderate attitudes, organizing programs, education, training, and workshops focusing on religious moderation, and evaluating learning outcomes to monitor the achievement of educational objectives. This study serves as a perspective and guideline for developing moderation values in Arabic language education in formal institutions such as madrasahs and non-formal institutions such as Islamic boarding schools (pesantren).